Influence of the matrix of the soil-rock mixture on deformation and failure behaviors of the slope based on material point method - Li, Xia; Tang, Shanyanqin; Zheng, Yong; Liu, Jie; Wang, Liejian; He, Kaiyuan; Jiang, Tao (Frontiers in Earth Science, 2022)
In this paper, the material point method (MPM) is used to explore the influence of matrix (namely soil) in the soil-rock mixture (SRM) on the stability of SRM slope. Firstly, a typical slope model is established, and a series of circular stone blocks with different sizes are generated inside the slope, then the SRM slope model is established. Next, the gravity is linearly loaded. When it is completed, the kinetic damping is applied, and the kinetic energy of the SRM slope is set to 0 to obtain the initial state of the slope. Then, the stability of the SRM slope under different soil cohesions and internal friction angles is simulated by MPM. The simulation results show that the stability of the SRM slope is more affected by cohesion than the internal friction angle. When the SRM slope enters the large deformation stage, there are both translational sliding and rotational sliding modes in the slope. The translational sliding is mainly the soil above the slope surface, and the SRM under the slope occurs rotational sliding.